The Use of Infographics to Enhance Reading Comprehension Skills among Learners - López Cupita, Lorena Andrea; Puerta Franco, Laura Milena (Colombian Applied Linguistics Journal, 2019)
This article describes a pedagogical intervention carried out at a public university in Colombia. A total of 26 psychology students, aged between 19 and 26 years old, taking English classes for academic purposes, and in their fourth semester, participated in this study. This intervention was implemented for an academic semester and aimed to help learners develop their English reading skills—from literal to critical comprehension of short academic texts— through the use of infographics, which are visual tools that combine texts and graphs to help users communicate information. Teachers used students’ infographics to assess their understanding of short academic texts in English, and they interviewed students to learn their opinions on the intervention. Further, teachers implemented a colour-coding technique in interview transcripts to show relevant patterns in the student opinions. This data analysis indicated that the students clearly understood the ideas from the texts because they were able to go beyond reading to dynamise information in the infographics while using the visual aids as mediators in expressing their ideas. In conclusion, the infographics were beneficial in developing the students’ reading skills. They presented an opportunity for the students to paraphrase main ideas from the texts and represent their understanding of the readings. In addition, this pedagogical intervention was useful for teachers because it enabled them to explore reading comprehension using a new strategy that might be helpful in English classes.